Program Acara Feature “Perempuan Bercerita” di iNews Semarang Sebagai Produser Pada Episode 2, 5, dan 10, Program Director, Reporter, Penulis Naskah, Juru Kamera, dan Editor - Santa Cicilia Sinabariba; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Television nowaday has a high penetration compared with other mass media consumed by the community, including local television iNews Semarang. As one of the local television, iNews present as news television by displaying information about Central Java with broadcasting hour for two hours at 09.00-11.00 WIB every day. This is a challenge for journalistic people to produce quality programs to audiences, in addition to the news program that became the main item iNews Semarang. For that, an innovative and new program for viewer features by presenting the program. Perempuan Bercerita comes with a feature format and presents a program that raises two inspiring female figures in each episode. This program is present to show and show the existence of women in Semarang in various areas of life, including how women take role in society by raising the story of woman in Semarang according to different theme in each episode. In producing this program, teams are divided to perform different responsibilities in each episode from pre-production, production, and post-production processes to producers, program directors, reporters, scriptwriters, cameramen, editors and dubber so that all team members get different experiences in each episode. Perempuan Bercerita aired 13 episodes at iNews Semarang every Monday at 10.00 am which aired from March 5, 2018 until June 4, 2018. Through this program, people are expected to get information and education and get the spirit and inspiration to continue to work and play an active and positive role in the environment. In addition, it also provides new referrals to local television to bring new programs to the audience.